PENGARUH CURRENT RATIO, DEBT TO ASSET RATIO DAN TOTAL ASSET TURN OVER TERHADAP RETURN ON ASSETS PADA KOPERASI DI KABUPATEN GRESIK TAHUN 2013-2015 (STUDI PADA KOPERASI YANG MELAPORKAN DI DISKOPERINDAG) - INNAWATI, INNAWATI (Jurnal Manajerial, 2019)
This study aims to examine the Effect of Current Ratio, Debt to Asset Ratio and Total Asset of Turn Over On Return on Assets in cooperatives in Gresik Regency in 2013-2015 (Studies in Cooperatives reported in Diskoperindag). The population in this study were 28 coopertives. which includes cooperatives that get profit. The sample uses saturated samples, where all members of the population are used as samples and obtain data from 84 cooperatives during the 3-year observation period. The analysis technique used is multiple linear regression and hypothesis testing using partial t test. The result of the research with the regression equation Y = a b1X1 b2X2 b3X3, shows that the current ratio is positively related to return on assets, because the coefficient is positive 4.05E-009, while the debt to asset ratio has a negative relationship with return on assets because the coefficient is negative - 0.001 and the total asset turnover also has a positive relationship with return on assets because the positive coefficient is 0.001. While the partial current ratio does not affect the return on assets in cooperatives that make a profit in Diskoperindag in Gresik district in the 2013-2015 period, because the t-count value is 0.019 smaller with t-table that is equal to 1.990. And partially the debt to asset ratio negatively affects return on assets in cooperatives that report consistent financial statements and cooperatives that benefit at Diskoperindag in Gresik regency for the period 2013-2015, because the t-count value is -4.259 smaller with t -table equal to 1.990. And total asset turn over partially affects return on assets in cooperatives that report consistent financial statements and cooperatives that benefit from Gresik District Diskoperindag for the 2013-2015 period.